2022
DOI: 10.1002/cam4.5348
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a cost‐effective virtual reality educational tool to reduce anxiety and improve set‐up accuracy in radiotherapy patients

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…However, the evidence has not yet resulted in standardized guidelines, probably motivated by insufficient methodological quality and the lack of randomized clinical trials with robust methodological designs [21]. In this context, the development of economic evaluations in the area of virtual reality applied to the rehabilitation of patients with Parkinson's is crucial, as is occurring in other medical areas where virtual reality is being applied [22][23][24][25][26], to identify its cost-effective relationship with other relevant diagnostic and treatment alternatives in terms of resource consumption and effectiveness [27,28]. Incremental cost-effectiveness analyses can be very useful for evaluating the application of virtual reality in the rehabilitation of Parkinson's patients, determining whether the additional outcomes obtained (improvement of motor function, quality of life, functional independence, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…However, the evidence has not yet resulted in standardized guidelines, probably motivated by insufficient methodological quality and the lack of randomized clinical trials with robust methodological designs [21]. In this context, the development of economic evaluations in the area of virtual reality applied to the rehabilitation of patients with Parkinson's is crucial, as is occurring in other medical areas where virtual reality is being applied [22][23][24][25][26], to identify its cost-effective relationship with other relevant diagnostic and treatment alternatives in terms of resource consumption and effectiveness [27,28]. Incremental cost-effectiveness analyses can be very useful for evaluating the application of virtual reality in the rehabilitation of Parkinson's patients, determining whether the additional outcomes obtained (improvement of motor function, quality of life, functional independence, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Zhao et al, to evaluate the effectiveness, carried out tests with a group of 120 patients undergoing radiotherapy. These patients were divided into two groups: one control and one intervention (49). In another study, Hao et al They identified a total of 799 patients with different types of cancer, and through a pooled analysis, we sought to determine whether the use of virtual reality showed significant improvements in treatment (42).…”
Section: Figure 5 Mention Of Cyberdisease In Studiesmentioning
confidence: 99%